Penggambaran Peran Ratu Maha Maya pada Relief Lalitavistara Candi Borobudur dalam Perspektif Life Course - Dewi Fatimah Adzir Maulana; Chaidir Ashari (AMERTA, 2025)
Abstract. Depiction of the Role of Queen Maha Māyā in the Lalitavistara Relief of Candi Borobudur from a Life Course Perspective. This study discusses the depiction of Queen Maha Māyā by highlighting the role of the body as the center of social, biological, and spiritual experiences. The issue raised is how the concept of Queen Maha Māyā's life course is depicted in the Lalitavistara reliefs at Borobudur Temple. The purpose of this study is to examine how the depiction of Queen Maha Māyā visualized in the relief contains meanings related to the transition of her role and status in a spiritual and social context. The study was conducted through literature review and Panofsky's iconographic method, accompanied by a life course and embodiment theory approach. The results of the analysis show that the iconographic visualization of Queen Maha Māyā shows different depictions before and after pregnancy in accordance with the stages of her life course. This study also shows that the symbolization of motherhood in the relief is more than just aesthetics, but also a reflection of spiritual and socio-cultural values that uphold the position of women.  Keywords:  Life course, Embodiment, Borobudur, Buddha   Abstrak. Penelitian ini membahas penggambaran Ratu Maha Māyā dengan menyoroti peran tubuh sebagai pusat pengalaman sosial, biologis, dan spiritual. Permasalahan yang diangkat adalah bagaimana penggambaran konsep life course Ratu Maha Māyā yang dipahatkan pada relief lalitavistara di Candi Borobudur. Tujuan penelitian ini adalah untuk menelaah bagaimana penggambaran Ratu Maha Māyā yang divisualisasikan dalam relief mengandung makna yang berkaitan dengan transisi peran dan statusnya dalam konteks spiritual dan sosial. Kajian dilakukan dengan studi kepustakaan serta metode ikonografi Panofsky disertai pendekatan teori life course dan embodiment. Hasil analisis menunjukkan bahwa visualisasi ikonografis Ratu Maha Māyā memperlihatkan perubahan penggambaran yang berbeda pada tahap sebelum dan setelah kehamilan sesuai dengan tahapan life course. Studi ini juga menunjukkan bahwa simbolisasi keibuan dalam relief lebih dari sekadar estetika, melainkan pula refleksi nilai spiritual dan sosial budaya yang menjunjung tinggi posisi perempuan.   Kata kunci: Perjalanan hidup, Ketubuhan, Borobudur, Buddha